Influence of seabed proximity on the vibration responses of a pipeline accounting for fluid-structure interaction. (1st January 2019) - Ribeiro Neto, H.; Cavalini, A.; Vedovoto, J.M.; Silveira Neto, A.; Rade, D.A.
Highlights: The influence of the fluid–structure-seabed interaction is remarkable. A numerical pluck test was performed to determine natural frequencies underwater. Lock-in is observed. The frequencies of displacements are correlated with those of vortex shedding. Interesting anomalies were observed for some mid-span gaps due to nonlinearities. Abstract: Cylindrical bodies subjected to external flow can vibrate due to the fluctuations of the forces induced by vortex shedding. The way these coherent fluid flow structures are formed and how they excite the structure depends on parameters, such as the Reynolds number, the reduced velocity, and the geometry e.g., the proximity of the structure to other bodies. These vibrations change the drag and lift forces by means of a nonlinear interaction. In addition, vibrations can cause crack nucleation and propagation in the structure. This is especially important when oil or natural gas is being transported in pipe-like structures, subjected to waves and sea currents. The present paper aims to characterize the influence of the proximity of the seabed on the fluid–structure interaction, considering horizontal pipes anchored by dunes. The simulations were undertaken for a nominally horizontal, elastic pipeline, 42 m in length and 0.273 m in diameter, with a mid–span static sag of 1.06 m due to self-weight. Seven different distances between the pipeline and the seabed were tested. The structural and fluid-dynamic models were coupled numerically, which allows the simulation and analysis of the flow using a single computational tool. The equations modeling the flow were solved in an Eulerian domain, while the surface of the immersed body was represented by a set of Lagrangian points. The immersed boundary method was used to impose a Dirichlet boundary condition on the Eulerian domain at the boundary between the structure and the fluid. It was also used to determine the fluid dynamic forces acting on the structure. An in-house three-dimensional computational framework was developed to simulate the turbulent incompressible flow subjected to fluid–structure interaction in conjunction with a beam modeled according to Timoshenko's theory. The obtained results are consistent, as expected for this problem.